Preparation of polyaniline/TiO₂ photovoltaic solar cell / Syed Lukhman ...[et al.] - Lukhman, Syed; Natar, Nadiah; Ghani, Nureel; Shukor, Amira; Nazeri, Syazana; Ikhwan, Syahirul; Badri, Afzalina; Hamzah, Raihan; Rosli, Afiq; Razak, Sharin; Izhan, Wan (Faculty of Applied Sciences, 2021)
Polyaniline (PANI) and Kronos C doped Titanium dioxide (TiO2) was fabricated as PANI/TiO2 solar cell and reported on its simple photovoltaic performance detected by using voltameter and tested for stability for 12 months. The PANI and TiO2 were coated onto different indium tin oxide (ITO) glass plates by using a drop-casting method and sandwich attached for simple solar cell preparation. PT4 sample was the optimum solar cell with 0.2: 0.2 g of PANI: TiO2 ratio under 2 cm2 surface area based on the highest voltage produces from 100 mW cm-1 of light intensity metal highlight lamp. No voltage was detected for PT7 where the single layer TiO2 coated without PANI attached for solar cell system using same fabrication. It shows that PANI has a significant role in functionalizing the photovoltaic system. The C-N stretching of aromatic amine and C-N stretching for the benzenoid at peaks of 1222 and 1166 cm-1 respectively in FTIR spectra has confirmed the PANI structure supported by an XRD pattern. TP4 has the highest photovoltaic performance compared to other types of TiO2 based on the electron lifetime (τe) and the voltage produced was sustained up to 12 months.